Pengaruh Sistem Informasi Manajemen dan Motivasi Kerja Terhadap Kinerja Karyawan di UPTD Instalasi Farmasi Kabupaten Tangerang - wulandari; merrisa fermica iskandar; ariyatia arief (Universitas Tangerang Raya, 2022)
Abstract— This study aims to determine the effect of Management Information Systems and Work Motivation on Employee Performance in UPTD Pharmacy Installation in Tangerang Regency partially or simultaneously. In this study there were a total sample of 50 respondents who used a saturated sample. This study uses a quantitative method. The results partially show that there is a positive and significant value of the variable X1 Management Information System on Employee Performance with t count of 7.672 and variable X2 of Work Motivation has a positive and significant value on employee performance with t count of 6.131. The results simultaneously show that the Management Information System and Work Motivation have a positive and significant effect on employee performance with the Fcount of 45.206. These results indicate that the Management Information System and work motivation together have a positive and significant effect on employee performance. In this study the variable X1 Management Information System which has the most dominant influence on employee performance at the UPTD Pharmacy Installation, Tangerang Regency.